"Media Addiction" in a 10-Year-Old Boy. Issue 1 (February 2017) - Brown, Scott; Scharf, Michael A.; Bustos, Cristina; Chavira, Denise; Stein, Martin T.
Abstract : CASE: Bryan is a 10-year-old boy who is brought to his pediatrician by his parents with concerns about oppositional behaviors. Bryan's parents report that he has always been hyperactive and oppositional since a very young age. He has been previously diagnosed with attention-deficit hyperactivity disorder and has been treated with appropriate stimulant medications for several years; however, despite this, his parents feel increasingly unable to manage his difficult behaviors. He refuses to do chores or follow through with household routines. He refuses to go to bed at night. His family feels unable to take him to public places because he "climbs all over everything." At school, he acts up in class, is often disruptive, and requires close supervision by teachers. He was recently kicked off of the school bus. He has very few friends, and his parents state that other children do not enjoy to be around him. Bryan's parents also report that he is "obsessed" with electronics. He spends most his free time watching TV and movies and playing computer games. He has a television in his bedroom because otherwise he "monopolizes" the family television. The family also owns several portable electronic devices that he frequently uses. Bryan insists on watching TV during meals and even that the TV stays on in an adjacent room while showering. He gets up early each morning and turns on the television. He refuses to leave the house unless he can take a portable screen device with him. His parents admit to difficulty placing limits on this behavior because they feel it is the only way to keep his other behaviors under control. His mother explains "it is our only pacifier" and that attempts to place restrictions are met with explosive tantrums and have thus been short lived. These efforts have also been impeded due to the habits of his parents and older sibling, who also enjoy spending a significant amount of time watching television.